No fresh water - no future - Chinnan, K. Pandimuruga (2004)
India is heading towards a freshwater crisis mainly due to improper management of water resources and environmental degradation which has led to a lack of access to safe water supply to millions of people. This freshwater crisis is already evident in many parts of India varying in scale and intensity depending mainly on the time of the year. - Reproduced.
Keywords: Water supply - India; Water supply